2021
DOI: 10.1088/1361-6668/ac1c15
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration tuning of the voltage modulation depth in YBa2Cu3O 7−δ nanowire-based SQUIDs

Abstract: Oxygen electromigration applied to a YBa 2 Cu 3 O 7−δ nanowire can be used to tune its electrical properties. Here, we apply electromigration to YBCO nanowire-based superconducting quantum interference devices (SQUIDs) and study its effect on the voltage modulation depth of the devices. Using a dc electromigration current we replenish the oxygen of the weak links, improving the critical current symmetry of the SQUIDs. AC current electromigration is used to reduce the doping level of the weak links, thus reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The current densities circulating across the device upon application of V write range between 1 kA • cm −2 and 10 kA • cm −2 , based on the measured currents and the section of the YBCO channel. However, these current densities are well below the value typically required to produce electromigration in YBCO (∼7 MA • cm −2 ) [33][34][35][36]. Consequently, it is unlikely that oxygen displacement due to electron collisions may explain the resistance increase and T C depression observed in figure 5.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The current densities circulating across the device upon application of V write range between 1 kA • cm −2 and 10 kA • cm −2 , based on the measured currents and the section of the YBCO channel. However, these current densities are well below the value typically required to produce electromigration in YBCO (∼7 MA • cm −2 ) [33][34][35][36]. Consequently, it is unlikely that oxygen displacement due to electron collisions may explain the resistance increase and T C depression observed in figure 5.…”
Section: Discussionmentioning
confidence: 78%
“…One of the possible oxygen-control approach consists of circulating large current densities, as reported in thin films and nanoconstrictions [30][31][32][33][34][35]. In these experiments, it was shown that a sufficiently large current (typically above 7 MA • cm −2 ) [33][34][35][36] can produce direct electromigration of the different atomic species. It has also been shown that, under certain conditions, the local heating produced by lower current densities can lead to thermomigration of oxygen ions [34,37].…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests that low frequency AC‐excitations may represent an effective way to increase the resistance of the transport bridge in a controlled fashion. [ 14,19 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the model permits us to explore the influence of different parameters such as initial oxygen concentration, oxygen disorder, and activation energy, which would require a colossal effort to address experimentally. These findings might shed light on the recent investigation of DC and AC electromigration in YBCO [ 14,19 ] and could be extended to explore the memristive properties of this material [ 25 ] or the electrical doping of Bi 2 Sr 2 CaCu 2 O 8−δ . [ 26 ] The close correlation between experiments and theory may encourage further research to explore the predictive power of the modeling to analyze the retention time and endurance of memristive devices based on oxygen motion and the effect of degassing caused by oxygen out‐diffusion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation